PENGARUH DIFERENSIASI PRODUK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN LAPTOP LENOVODI KOTA BATAM - Vinny; Suhardi (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2020)
This research was conducted to determine the effect of product differentiation and product quality on Lenovo laptop purchasing decisions in Batam City. This research is a quantitative study and data obtained through questionnaires. The population of this study is from Lenovo Laptop sales data from several laptop shops in Batam City in 2019. The number of samples in this study were 198 people. Then the questionnaire distributed by researchers to respondents was 198 respondents. The data collection technique used is the Purposive Sampling technique, which means taking a sample based on consideration from a group of experts. Primary data collected from the questionnaire results distributed. The results of this study indicate that the product differentiation variable has a positive effect of 0.147 and a significance of 0.000 <0.05 and a value of 4.599> t table 1.97720 on the variable of Lenovo laptop purchase decisions in Batam City. Product quality variable has a positive effect of 0.693 and a significance of 0.000 <0.05 and tcount 12.287> t table 1.97720 on the Lenovo laptop purchase decision variable in Batam City. The product differentiation and product quality variables together have a positive and significant effect on the purchase decision variables of Lenovo laptops in Batam City with a significance of 0,000 <0.05 and Fcount 385,781> Ftable 3.04